Computational modeling of temperature and relative humidity effects on concrete expansion due to alkali–silica reaction. (November 2021) - Yang, Lifu; Pathirage, Madura; Su, Huaizhi; Alnaggar, Mohammed; Di Luzio, Giovanni; Cusatis, Gianluca
Abstract: This paper presents a constitutive model for the simulation of temperature and relative humidity effects on concrete expansion due to Alkali–Silica Reaction (ASR). The model was formulated within the multiphysics framework of the Lattice Discrete Particle Model (LDPM). LDPM simulates concrete internal structure at the mesoscale defined as the length scale of coarse aggregate pieces. As such it accounts for the heterogeneous character of ASR expansion, cracking and damage, creep, hygrothermal deformation as well as moisture transport and heat transfer. The overall framework was calibrated and validated by comparing several numerical simulations with a large database of experimental data gathered from the literature. The proposed model is able to capture accurately all available experimental evidence, including: (a) the increase of expansion rate for increasing temperature and its marked decrease for decreasing relative humidity; and (b) both increase or decrease of ASR ultimate expansion as function of temperature.